Characterization of Pseudomonas spp. and Associated Proteolytic Properties in Raw Milk Stored at Low Temperatures - Meng, Lu; Zhang, Yangdong; Liu, Huimin; Zhao, Shengguo; Wang, Jiaqi; Zheng, Nan (Frontiers in Microbiology, 2017)
Milk spoilage is caused by the presence of proteolytic enzymes produced by Pseudomonas spp. during storage at low temperatures. The aim of this study was to identify Pseudomonas spp. in raw milk and investigate their associated proteolytic properties at low temperatures. Raw milk samples (n = 87) were collected from 87 bulk tanks in Shaanxi Province in China. Pseudomonas spp. were identified using Pseudomonas specific 16S, universal 16S rRNA sequencing, and rpoB gene sequencing. The proteolytic properties of Pseudomonas spp. were examined using milk agar, quantitative trinitrobenzenesulfonic acid (TNBS) assay, and by the presence of alkaline metallopeptidase gene (aprX). A total 143 isolates from all 87 samples were confirmed as Pseudomonas, and were identified as belonging to 14 Pseudomonas species. Of these, 40 (28.0%) isolates revealed proteolysis on milk agar at 2°C, 74 (51.8%) at 4°C, 104 (72.7%) at 7°C, and 102 (71.3%) at 10°C. However, proteolytic activity of 45 (31.5%) isolates exceeded 2 μmol of glycine equivalents per mL at 7°C, followed by 43 (30.1%) at 10°C, 18 (12.6%) at 4°C, and 7 (4.9%) at 2°C. The results reveal proteolytic activity of Pseudomonas spp. present in milk and their spoilage potential at different temperatures.